Leakage behavior of toxic substances of naphthalene sulfonate-formaldehyde condensation from cement based materials. (1st February 2020) - Gu, Linan; Li, Haoxin; Yang, Xiaojie; Dong, Biqin; Wen, Zhaoyin
Abstract: Naphthalene sulfonate-formaldehyde condensatation (NSF) is the main component of the naphthalene based water reducers for cement based materials, as well as an organic substance with potential toxicity. However it is still uncertain whether it can leak from the cement based materials. In this work, the leakage ratio and adsorption behavior of NSF from various cement based materials such as the different water/cement (w/c) ratio, NSF content, types of cementitious materials as well as at different hydration time were evaluated. The product components of the cement based materials cured for different times were also quantified to explore the mechanisms which are responsible for the leakage and adsorption behaviors. The results indicate that more NSF, lower w/c ratio and less mineral admixture decrease the NSF leakage ratio. The leakage ratio of NSF from cement paste mixed 0.3% NSF is up to 50.8% at 0.5 h, and it decreases to 31.0% at 28 d. The leakage ratio of NSF from cement paste decreases as the hydration time prolongs. The lower leakage ratio corresponds to the higher adsorption capacity. Less adsorption capacity and thinner adsorption film imply that lower temperature and mineral admixture decrease the NSF adsorption behavior. When 0.3% NSF is added into the cement paste, the adsorption amount and NSF layer thickness are 5.53 mg/g and 0.98 nm, 5.87 mg/g and 4.7 nm at 0.5 h and 28 d respectively. The result demonstrates that the adsorption behavior of NSF in cement significantly increases at the initial several hours and gradually stabilizes after the first day. The X-ray powder diffractometer (XRD) results show that the contents of tricalcium silicate (C3 S) and dicalcium silicate (C2 S) continuously decline and the amorphous phases and ettringite (AFt) increase rapidly in the early stage. NSF adsorption and leakage behaviors are closely related to the hydration process of cement. These results indicate that NSF can definitely leak from the cement based materials and thus the NSF potential environmental pollution cannot be ignored. At least, it should be restricted or cautious to produce the water tower and pipe concrete structure with it. These results will sever as a theoretically reference for the pollution control as well as better application of NSF in cement-based materials. Highlights: More NSF, lower w/c ratio and less admixture decrease the NSF leakage ratio. NSF leakage ratio is up to 50.8% at 0.5 h, and it decreases to 31.0% at 28 d Adsorption amount and thickness are 5.53 mg/g and 0.98 nm at 0.5 h respectively. Adsorption amount and thickness are 5.87 mg/g and 4.7 nm at 28 d NSF leakage behavior is closely related to hydration time and products.